Impact Response of Novel Fibre-Reinforced Grouted Aggregate Rubberized Concrete - Avudaiappan-, S (Springer Verlag, 2019)
The consumption of waste tyre rubber in concrete is considered to be a critical factor addressing environmental issues and sustainability. Rubberized concrete is a novel building material that poses high energy absorption capacity compared to normal concrete and finds many applications in civilian infrastructures. The concept of impact strength of fibre-reinforced grouted aggregate rubberized concrete (FRGARC) has been pioneered in this study. In the fabrication of FRGARC, combination of steel fibres and treated rubber aggregates was placed in the formwork, and then, a flowable grout was injected to fill the voids. The rubber used in this experiment was pre-treated by immersing in water with 10% NaOH solution for a time period of 0.5 h. The variables examined in this investigation are crumbed rubber aggregate replacement ratios of 5%, 10%, 15%, 20%, 25% and 30% with three different water/binder ratios (0.45, 0.50 and 0.55). Hooked-end steel fibres were used at a constant dosage of 0.5% volume of concrete. The density reduction factor, compressive strength (CS), number of impact that induced initial crack and failure, initial crack and failure energy increasing factor of FRGARC were studied. Linear and power regression equations were developed to assess the density reduction factor and initial crack and failure energy increasing factor. FRGARC exhibits reduction in CS with increasing rubber content, and it significantly contributes to the enhancement of initial crack and failure impact energy absorption capacity. © 2019, King Fahd University of Petroleum & Minerals.